2019
DOI: 10.3389/fevo.2019.00484
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Shotgun Sequencing Detects Greater Lichen Fungal Diversity Than Amplicon-Based Methods in Environmental Samples

Abstract: In this study we demonstrate the utility of whole genome shotgun (WGS) metagenomics in study organisms with small genomes to improve upon amplicon-based estimates of biodiversity and microbial diversity in environmental samples for the purpose of understanding ecological and evolutionary processes. We generated a database of full-length and near-full-length ribosomal DNA sequence complexes from 273 lichenized fungal species and used this database to facilitate fungal species identification in the southern Appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…A previous study has successfully identified fungi in the animal metagenomes containing 71 fungal species from 39 datasets using newly developed FindFungi program [ 33 ]. Other study demonstrated that DNA shotgun sequencing was superior to detect lichen fungal diversity in environmental samples as compared to amplicon based methods [ 34 ]. RNA-sequencing with poly(A) selection cannot be used for the majority of bacteria, and many viruses without poly(A) tails cannot be selected by oligo dT for mRNA preparation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has successfully identified fungi in the animal metagenomes containing 71 fungal species from 39 datasets using newly developed FindFungi program [ 33 ]. Other study demonstrated that DNA shotgun sequencing was superior to detect lichen fungal diversity in environmental samples as compared to amplicon based methods [ 34 ]. RNA-sequencing with poly(A) selection cannot be used for the majority of bacteria, and many viruses without poly(A) tails cannot be selected by oligo dT for mRNA preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling substrata (soil, wood, leaves, and roots) has great potential for documenting the presence of fungi even in the absence of visible spore bodies (e.g., mushrooms). Mycologists use eDNA to assess the potential conservation value of sites (Griffith, Cavalli, & Detheridge, 2019) and monitor, document, and model the distribution of taxa (Hao, Guillera-Arroita, May, Lahoz-Monfort, & Elith, 2020;Keepers et al, 2019;Suz et al, 2015).…”
Section: Box 5 Horizon Scanmentioning
confidence: 99%
“…All reads were filtered using TRIMMOMATIC v0.33 (Bolger et al 2014) before mapping to remove low quality reads and/or included contamination from Illumina adaptors using the following parameters: ILLUMINACLIP; LEADING:3; TRAILING:3; SLIDINGWINDOW:4:15; and MINLEN:36. Previous studies have used assembled metagenomic contigs (Keepers et al 2019) or mapped fungal reads to a fungal protein database (LaBonte et al 2018) to provide crucial insight into fungal diversity in lichens and deciduous trees. Given the expected low coverage for fungi potentially co-occurring with a lichen thallus in short reads generated for this study, we chose to focus on the well-known repeat region which includes the standard fungal DNA barcode, the ITS region of the nuclear ribosomal DNA (nrDNA) (Schoch et al 2012).…”
Section: Sequence Analysismentioning
confidence: 99%